Pengaruh Kebijakan Pemerintah terhadap Keberlanjutan Industri Migas di Era Transisi Energi - Edy Soesanto; Arya Raihan; Setya Angga (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2025)
The energy transition era initiated by the Indonesian government through strategic policies such as the National Energy Plan (Rencana Umum Energi Nasional or RUEN) and the 2060 Net Zero Emission target has significantly impacted the sustainability of the oil and gas (O&G) industry. These policies encourage the industry to adopt low-carbon technologies, diversify energy portfolios, and enhance operational efficiency. Major oil and gas companies such as Pertamina and MedcoEnergi have started transforming their operations by investing in renewable energy projects such as bioenergy, solar power, and hydrogen initiatives. Carbon capture and storage (CCS) technology has also emerged as a key solution to reduce emissions from O&G operations.However, this transition faces significant challenges, including high investment requirements, regulatory uncertainty, and competition from renewable energy. Despite these obstacles, government policies have proven effective in driving innovation and accelerating the integration of the oil and gas industry into a low- carbon economy[1]. This article aims to analyze the impact of government policies on the sustainability of Indonesia's oil and gas industry and provide insights into the strategic role of the sector in supporting the national energy transition..